Adaptive fuzzy backstepping control of three-phase active power filter. (December 2015) - Hou, Shixi; Fei, Juntao
Abstract: A backstepping controller (BC) and an adaptive fuzzy backstepping controller (AFBC) are proposed for three-phase active power filter (APF) in this paper. Firstly, the dynamic model for APF is build in which both the system parameter variations and external disturbance are considered. Then, the backstepping method is applied in the design of current control system to deal with the nonlinearity of APF. Moreover, the AFBC is developed by combining the backstepping approach with adaptive fuzzy strategy to attenuate the effect of parameter uncertainties and external disturbances. Fuzzy logic system is designed to estimate the unknown nonlinear function in the AFBC where the parameters are adjusted online by the adaptive law derived from the Lyapunov stability analysis to guarantee the tracking performance and stability of the closed-loop system. Simulation studies using the MATLAB/SimPower Systems Toolbox demonstrate that the proposed control strategies exhibit excellent performance in both steady state and transient operation. Highlights: An adaptive fuzzy backsepping control strategy for the APF is presented. A fuzzy system is used to approximate the unknown nonlinear dynamics. The parameters can be adaptively updated based on the Lyapunov analysis. The stability of the closed-loop system can be guaranteed. Simulation studies demonstrate the high performance of the control strategies.